Kingship’s Impact on "Arabic Marsia" - Hussaini, Fareed; Hadi, Ahmad Hussain; Azmi, Azmat Shehzad (sourcecoder, 2024)
From the very beginning of the world, there are two forces existed, one is Rehmani and the second is satanic. Kingdoms and Dictatorships often proved themselves as representative of the II force. Mourning and sorrowness is the weapon of poor and depressed people who show the patience against cruelty and do catharsis. The Marsia was a form of Arabic literature which kept the departed soul alive by poetry. When Islamic Khilafat changed into Malukiat (Kingdom) Marsia became a danger for it. Kings thought that by this sort of poetry the event of karbala will remain fresh in people’s mind which can be fatal to their so they did not allow to poets to create this form of poetry. They, by using force and offering incentives, discouraged artists to say Marsia. In this article, efforts have been made to prove the impacts the impacts of Malukiat over this artistic form.